Quantum Dot-Doped Glasses and Fibers: Fabrication and Optical Properties - Dong, Guoping; Wang, Haipeng; Chen, Guanzhong; Pan, Qiwen; Qiu, Jianrong (Frontiers in Materials, 2015)
Quantum dot-doped glasses have been the hotspot for their excellent electronic and optical properties. Owing to its tunable and broadband near-infrared (NIR) emission by controlling the size and distribution of QDs, QD-doped glasses and fibers are potentially applied in photoelectric devices. In this review, we mainly introduce the preparation, tunable emission, and multi-wavelength optical amplification of QD-doped glasses. Due to their excellent optical performances, the fabrication of QD-doped glass fibers is also presented, containing the successful fabrication of QD-doped glass fibers with tunable NIR emission. Furthermore, the achievements and existing problems about QD-doped glasses and fibers are also proposed with several prospects. These QD-doped glasses and fibers show promising applications as the gain medium of NIR broadband fiber amplifiers and tunable fiber lasers.